microRNAs in viral acute respiratory infections: immune regulation, biomarkers, therapy, and vaccines - Stephen A. Leon-Icaza; Mingtao Zeng; Adrian G. Rosas-Taraco (ExRNA)
Abstract MicroRNAs (miRNAs) are single-stranded RNAs of 17–24 nt. These molecules regulate gene expression at the post-transcriptional level and are differentially expressed in viral acute respiratory infections (ARIs), which are responsible for high morbidity and mortality around the world. In recent years, miRNAs have been studied in order to discover anti-viral ARI drug targets as well as biomarkers for diagnosis, severity, and prognosis. This review presents an analysis of the regulatory response to viral ARIs of miRNAs, including their participation in the innate immune response, their utility as biomarkers, and their potential for future therapies and vaccine development.